Identifying Patterns of Role Negotiation in Blended Families and Their Effects on Cohesion and Identity - Al-Taie, Zainab; Abdulhussein, Omar (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to explore the patterns of role negotiation in blended families and examine their influence on family cohesion and identity formation. Methods and Materials: A qualitative research design was employed using semi-structured interviews with 26 participants from blended families in Iraq, including parents, step-parents, and children. Participants were selected purposively to ensure diversity in age, gender, and family role, with inclusion criteria requiring at least two years of experience in a blended family. Data collection continued until theoretical saturation was reached. All interviews were audio-recorded, transcribed verbatim, and analyzed thematically with the aid of NVivo 14 software. Credibility was enhanced through member checking and audit trails, while thick descriptions ensured transferability. Findings: Analysis revealed three overarching themes: (1) Role Negotiation Processes, encompassing parental boundaries, household responsibilities, communication patterns, and cultural influences; (2) Cohesion and Emotional Climate, including bonding among step-siblings, emotional connections between parents and children, feelings of belonging, and loyalty conflicts; and (3) Identity Formation and Adjustment, covering dual belonging, adolescent autonomy, the influence of past family structures, and resilience strategies. Participant narratives highlighted frequent conflicts around fairness, authority, and inclusion, with cultural norms and extended kin networks shaping both tensions and adaptation. Successful negotiation fostered cohesion and strengthened shared identity, while unresolved conflicts generated exclusion and fragmented identities. Conclusion: The findings underscore that role negotiation is a central process in determining the stability, cohesion, and identity development of blended families. Effective communication, cultural sensitivity, and shared rituals emerged as key facilitators of integration. Interventions should focus on clarifying roles, managing loyalty conflicts, and promoting adaptive coping strategies to strengthen resilience and family cohesion in blended family contexts.